Experiential entrepreneurship education via US films: why and how. Issue 6 (6th October 2020) - Liguori, Eric; Muldoon, Jeff; Bendickson, Josh
Abstract : Purpose: Experiential education is key if the authors as scholar-educators are to empower the next generation of students to recognize opportunities, exploit them and succeed in entrepreneurship. Experiences facilitate the bridge between theory and practice; experiencing something serves as the linking process between action and thought. Capitalizing on technological advances of the last two decades, this paper depicts how film can be (and why it should be) incorporated into entrepreneurship classrooms. Design/methodology/approach: The authors analyze the learning literature, broadly defined, to assess and articulate the experiential nature of film. More specifically, this paper establishes a framework for film as an experiential pedagogical approach, offering theoretical connections and best practice recommendations. In doing so, this paper assesses two feature films and provide educators with a guide for their use in the classroom. Findings: This paper establishes a framework for film as an experiential pedagogical approach, offering theoretical connections and best practice recommendations. It concludes with two actionable case examples, broad enough they are deployable in almost any entrepreneurship classroom, assuming English is the primary language. Originality/value: This paper brings to life a concept some have long assumed is effective, but the literature often neglects: the use of film as an experiential medium. In doing so, two new case examples are developed and available for immediate deployment into classrooms.